2015
DOI: 10.1017/jfm.2015.64
|View full text |Cite
|
Sign up to set email alerts
|

Weakly nonlinear analysis of Rayleigh–Bénard convection in shear-thinning fluids: nature of the bifurcation and pattern selection

Abstract: A linear and weakly nonlinear analysis of convection in a layer of shear-thinning fluids between two horizontal plates heated from below is performed. The objective is to examine the effects of the nonlinear variation of the viscosity with the shear rate on the nature of the bifurcation, the planform selection problem between rolls, squares and hexagons, and the consequences on the heat transfer coefficient. Navier’s slip boundary conditions are used at the top and bottom walls. The shear-thinning behaviour of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
51
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(58 citation statements)
references
References 59 publications
(85 reference statements)
6
51
1
Order By: Relevance
“…It is worth noting that in the Carreau fluid case, the heat transfer is increased with decreasing n as shown by Refs. and . Contrarily to the Herschel‐Bulkley model, in the Carreau case, the decrease in effective viscosity is larger when n decreases.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…It is worth noting that in the Carreau fluid case, the heat transfer is increased with decreasing n as shown by Refs. and . Contrarily to the Herschel‐Bulkley model, in the Carreau case, the decrease in effective viscosity is larger when n decreases.…”
Section: Resultsmentioning
confidence: 90%
“…It is not surprising as one knows that shear‐thinning fluids can involve subcritical bifurcation as shown in Refs. . A theoretical study has also shown the possibility of subcritical bifurcation in yield stress fluids in the case of the Rayleigh‐Bénard Poiseuille flow for low values of Reynolds number.…”
Section: Resultsmentioning
confidence: 94%
“…(27). These computations have been also made with no-slip boundary conditions at the horizontal walls by [17]. The same phenomenon occurs, though the critical values of the rheological parameters at which the bifurcation to rolls changes of nature is modified (again, see Eq.…”
Section: Introductionmentioning
confidence: 71%
“…In [17] it has been shown, with a weakly nonlinear analysis based on a spectral method, that, in this system, the nature of the bifurcation from the conduction state to convection rolls with a critical wavenumber depends on a single rheological coefficient…”
Section: Summary Of the Known Weakly Nonlinear Resultsmentioning
confidence: 99%
See 1 more Smart Citation